Vocabulary Learning Strategies, Vocabulary Knowledge and Reading Comprehension of EFL Undergraduate Students in Iran - Reza, Kafipour (2010)
The current study investigated the relationship among vocabulary learning strategies, vocabulary knowledge, and reading comprehension of Iranian undergraduate EFL students. In addition, the study tried to find the contribution of vocabulary learning strategies to vocabulary size and reading comprehension of the students. Fars province was selected according to cluster sampling. Data were collected from all 250 second year undergraduate EFL students. The collection of data was done in two different phases – quantitative and qualitative. In the quantitative phase of the study, the data were collected through a vocabulary learning strategy questionnaire adapted from Bennett (2006). A vocabulary size test developed by Nation (2007) and a TOEFL reading comprehension test were also used in the study. Data were also collected through interviews and journal writing in the qualitative phase of the study. Descriptive statistics showed that Iranian undergraduate EFL learners were medium strategy users. All different categories of vocabulary learning strategies were reported to be used at a medium level. However, the most frequently used strategies consisted of using monolingual dictionary, guessing meaning from context, connecting the word to its synonyms and antonyms, using new words in sentences, studying the sound of a word, using English language media, skipping or passing new words, repeating verbally, and taking note or highlighting. The least frequently used strategies included checking for L1 cognate, writing paraphrase using several new words, using physical action when learning a word, making word lists, studying the word with classmates, interacting with native speakers, and asking the teacher to check one’s definition. The students were found to have a vocabulary size of 5564 words. Then, Pearson Product Moment Correlation was conducted to find the relationships between variables. The Pearson correlation showed a positive correlation between vocabulary size and reading comprehension of the students. A positive correlation was also found between 14 vocabulary learning strategies and vocabulary size. However, multiple regressions showed that only 9 out of 14 strategies contributed to vocabulary size of the students. These strategies consisted of using physical action when learning a word, interacting with native speakers, taking note or highlighting, studying new words many times, using bilingual dictionary, using English language media, studying the word with classmates, studying the sound of a word, and repeating the word verbally. Pearson correlation also indicated positive correlation existed between 23 vocabulary learning strategies and reading comprehension. However, 5 out of 23 strategies were found to contribute to reading comprehension of the students. These strategies consisted of taking note or highlighting, using physical action when learning a word, asking the teacher to paraphrase or give synonym of new words,asking classmates for meaning, and remembering the word using its affixes and roots.